RFID Healthcare Item Tracking System (HITS) - Aini Syuhada, Md. Zain; Hanif, Mohammad Mohiddin (Universiti Teknologi MARA, Kedah, 2010)
Invention, Innovation & Design (IID Kedah 2010), 28th - 29th July 2010 organized by Universiti Teknologi MARA (UiTM), Kedah at SP Inn, Kedah.